2002
DOI: 10.1021/jm025551+
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First Nonpeptide Agonist of the GPR14/Urotensin-II Receptor:  3-(4-Chlorophenyl)-3-(2- (dimethylamino)ethyl)isochroman-1-one (AC-7954)

Abstract: A functional cell-based screen identified 3-(4-chlorophenyl)-3-(2-(dimethylamino)ethyl)isochroman-1-one hydrochloride (AC-7954, 1) as a nonpeptidic agonist of the urotensin-II receptor. Racemic 1 had an EC50 of 300 nM at the human UII receptor and was highly selective. Testing of the enantiopure (+)- and (-)- 1 revealed that the UII receptor activity of racemic 1 resides primarily in (+)-1. Being a selective nonpeptidic druglike UII receptor agonist, (+)-1 will be useful as a pharmacological research tool and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 20 publications
(25 reference statements)
0
37
0
Order By: Relevance
“…Nevertheless, the 3D information might be very useful for understanding the binding process of existing leads, as shown by docking studies performed with the nonpeptidic UII agonist AC-7954 (Lavecchia et al, 2005) (Fig. 11, compound 17; Acadia Pharmaceuticals, San Diego, CA; EC 50 : 316 nM for the racemic mixture) (Croston et al, 2002). Noteworthy, AC-7954 is the precursor of the potent UT agonists (+)-FL68 (EC 50 : 50 nM), a 6,7-dimethylated derivative of the lead compound (Lehmann et al, 2005), as well as (+)-FL104 (Fig.…”
Section: Design Of Nonpeptidic Urotensin II Receptor Agonists and mentioning
confidence: 99%
“…Nevertheless, the 3D information might be very useful for understanding the binding process of existing leads, as shown by docking studies performed with the nonpeptidic UII agonist AC-7954 (Lavecchia et al, 2005) (Fig. 11, compound 17; Acadia Pharmaceuticals, San Diego, CA; EC 50 : 316 nM for the racemic mixture) (Croston et al, 2002). Noteworthy, AC-7954 is the precursor of the potent UT agonists (+)-FL68 (EC 50 : 50 nM), a 6,7-dimethylated derivative of the lead compound (Lehmann et al, 2005), as well as (+)-FL104 (Fig.…”
Section: Design Of Nonpeptidic Urotensin II Receptor Agonists and mentioning
confidence: 99%
“…Palosuran has been identifi ed as a potent nonpeptide, orally active antagonist of the human UT receptor, binding studies showed the ligand to have 100-fold greater affi nity for human UT receptor over rat UT receptor [29]. Other synthetic ligands, e.g., agonists: AC-7954,1 [30] and antagonists: SB-706375 [31] have been identifi ed. For a review of UT receptor antagonists the reader is directed to [32].…”
Section: Introductionmentioning
confidence: 99%
“…Urotensin II has recently been shown to be upregulated in infarcted rat heart (28) and in congestive heart failure in humans (11), suggesting a possible role of urotensin II in cardiac remodeling. Agonists (8,17) and antagonists (2,12,24) for GPR14 have been assumed as tools for pharmacological research and potential drug leads for the treatment of cardiovascular diseases. These reports give rise to the hypothesis that rat myocardium contains GPR14 receptor, which may be responsible for the biological effects of urotensin II in this tissue.…”
mentioning
confidence: 99%